Comparison of CTDIw and Effective mAs as Predictors of Effective Dose in Thoracic CT Examinations: A Retrospective Analysis - Bilqis, Ayesha; Nurhanivah, Devi; Ramdhani, Saumi Zikriani; Soleh, Adeada Annisa Aulia (International Journal of Health, Medicine, and Sports, 2025)
This study compared the association between weighted computed tomography dose index (CTDIw) and effective milliampere-seconds (effective mAs) with the effective dose (ED) received by patients during thoracic computed tomography (CT) examinations. Retrospective data from breast cancer patients were obtained from The Cancer Imaging Archive (TCIA) and processed using IndoseCT software to extract CTDIw, effective mAs, and ED values. Descriptive statistics, scatter plots, and simple linear regression analyses were performed to evaluate the relationships between these parameters. The correlation between effective mAs and CTDIw was moderately strong (R² = 0.6774), consistent with the principle that higher tube current–time settings generally increase scanner-reported dose indices. CTDIw and ED showed a very strong correlation (R² = 0.978), reflecting the close link between standardized dose metrics and estimated patient dose. The correlation between effective mAs and ED (R² = 0.7505) was stronger than that between effective mAs and CTDIw, but still lower than the CTDIw–ED correlation. These results indicate that, in this dataset, CTDIw was a more consistent predictor of ED than effective mAs. While both parameters are relevant for dose assessment, CTDIw may be a more reliable reference for estimating ED in similar thoracic CT protocols. Although this analysis was limited to retrospective data from a specific patient group, the findings provide practical insights that can support protocol evaluation and dose optimization strategies. Further studies involving larger and more diverse datasets would be beneficial to confirm and extend these observations.